Sharing local knowledge - Muilerman, Sander; Schläpfer, Juanita (Technical Centre for Agricultural and Rural Cooperation, 2013)
Researchers now use ICTs to gather information more effectively from the field. ICTs also give them the possibility to help share knowledge in local communities